Stakeholder Dialogue as Agonistic Deliberation: Exploring the Role of Conflict and Self-Interest in Business-NGO Interaction. Issue 1 (January 2020) - Brand, Teunis; Blok, Vincent; Verweij, Marcel
ABSTRACT: Many companies engage in dialogue with nongovernmental organizations (NGOs) about societal issues. The question is what a regulative ideal for such dialogues should be. In the literature on corporate social responsibility (CSR), the Habermasian notion of communicative action is often presented as a regulative ideal for stakeholder dialogue, implying that actors should aim at consensus and set strategic considerations aside. In this article, we argue that in many cases, communicative action is not a suitable regulative ideal for dialogue between companies and NGOs. We contend that there is often an adversarial element in the relation between companies and NGOs, and that an orientation towards consensus can be in tension with this adversarial relation. We develop an alternative approach to stakeholder dialogue called 'agonistic deliberation.' In this approach, conflict and strategic considerations play a legitimate and, up to a certain point, desirable role.